I-Shape by shape: Real-world STEM learning in Malaysia - Connie Shin @ Connie Cassy Ompok; Jusiah Idang (Taylor & Francis Group, 2025)
While the intellectual health of a country begins in the home, children’s broader surroundings are crucial in making sure that every child has a good start. Experiences at home and in the community stimulate imaginations, encourage curiosity, and promote learning as children naturally explore the spaces around them. This article describes interactive geometry activities for young Malaysian learners inspired by a local landmark in Kota Kinabalu, Sabah.